Comparison of luminance distribution on the lighting surface of power LEDs - Czyżewski, Dariusz (Photonics Letters of Poland, 2019)
This work presents luminance distributions across the surface of mid- and high-power diodes. The changes in luminance on diode surfaces following changes in the observation angle were verified. On the basis of the conducted tests, non-uniform luminance distribution on LED surface for diverse observation angles (including the axial direction) was observed. Moreover, it was concluded that luminance changes is not in line with the Lambert’s law. As the result of the research it was also concluded that alterations of the power-supply conditions do not exert any significant impact on the gradient of luminance changes on the surfaces of examined LEDs. Full Text: PDF References J. Fan, J. Cao, Ch. Yu, Ch. Qian, X. Fan, G. Zhang, A design and qualification of LED flip Chip-on-Board module with tunable color temperatures, Microelectronics reliability, ISSN 0026-2714, Nº. 84, 2018, pp. 140-148, CrossRef K. Bonislawski, I. Fryc, The study on optical properties of LEDs used for vehicle control lighting, Przeglad Elektrotechniczny, 2012, ISSN 0033-2097, Vol. 88, Issue 3A, pp. 119-120 DirectLink T. Kawabata, Y. Ohno, Optical measurements of OLED panels for lighting applications, Journal of Modern Optics 60(14), 2013, pp. 1176-1186 CrossRef P. Pracki, U. Blaszczak, The issues of interior lighting on the example of an educational building adjustment to nZEB standard, IEEE Lighting Conference of the Visegrad Countries (Lumen V4), IEEE (17 November 2016) CrossRef P. Tabaka, Analysis of electrical parameters of prime set bulb equivalents suitable for dimming, Przeglad Elektrotechniczny, 2015, R. 91, No. 5, pp. 100-106, ISSN 0033-2097 CrossRef D. Czyżewski, The street lighting luminaires with LEDs. Przeglad Elektrotechniczny, 86, 2009, pp. 276-279 DirectLink C. C. Miller; Y. Zong; Y. Ohno, LED photometric calibrations at the National Institute of Standards and Technology and future measurement needs of LEDs, Proc. SPIE Vol. 5530, Fourth International Conference on Solid State Lighting; (2004) CrossRef D. Mozyrska Dorota; M. Wyrwas; I. Fryc, The determination of the LEDs colorimetric parameters, in the range of their operating temperature, Przeglad Elektrotechniczny, Vol. 88, Issue: 4A, 2012, pp. 232-234 CrossRef K. Baran, A. Różowicz, H. Wachta, S. Różowicz, D. Mazur, Thermal Analysis of the Factors Influencing Junction Temperature of LED Panel Sources, Energies, 12, 3941, 2019 CrossRef D. Czyżewski, Research on Luminance Distributions of Chip-On-Board Light-Emitting Diodes, Crystals 9(12), 645, 2019. CrossRef L. Zheng, Z. Guo, W. Yan, Y. Lin, Y. Lu, H.C. Kuo, Z. Chen, L. Zhu, T. Wu, Y. Gao, Research on a Camera-Based Microscopic Imaging System to Inspect the Surface Luminance of the Micro-LED Array. IEEE Access 6, 2018, 51329-51336. CrossRef S. Słomiński, Selected Problems in Modern Methods of Luminance Measurement of Multisource LED Luminaires. Light Eng. 24, 2016, pp. 45-50. DirectLink I. Fryc, P. Jakubowski, K. Kołacz, Analysis of optical radiation parameters of compact discharge HID lamps and LED COB modules used for illuminating shop windows, Przeglad Elektrotechniczny, 2017, R. 93, nr 11, pp. 186-189. CrossRef I. Fryc, Measurement techniques of optical LEDs properties performed with compliance conformity with CIE 127:2007 standard, Przeglad Elektrotechniczny, 2009,ISSN 0033-2097,Vol. 85,Issue:11,pp.317-319. DirectLink I. Fryc, T. Dimitrova-Grekow, An Automated System for Evaluation of the Quality of Light Sources, 2016 IEEE Lighting Conference of the Visegrad Countries (Lumen V4), IEEE (17 November 2016), CrossRef CIE 235:2019, Optical measurement of led modules and light engines, ISBN 978-3-902842-25-1, DOI: 10.25039/TR.235.2019. CrossRef D. Czyżewski, Investigation of COB LED luminance distribution, In Proceedings of the 2016 IEEE Lighting Conference of the Visegrad Countries (Lumen V4), IEEE (17 November 2016) CrossRef I. Rotscholl, K. Trampert; U. Krüger; F. Schmidt, Spectral near field data of LED systems for optical simulations, Proceedings SPIE Volume 11144,Phot. and Educ. in Measur. Sc. 2019, CrossRef